Whole Genome Sequencing, de Novo Assembly and Phenotypic Profiling for the New Budding Yeast Species Saccharomyces jurei. Issue 9 (1st September 2018) - Naseeb, Samina; Alsammar, Haya; Burgis, Tim; Donaldson, Ian; Knyazev, Norman; Knight, Christopher; Delneri, Daniela
Abstract: Saccharomyces sensu stricto complex consist of yeast species, which are not only important in the fermentation industry but are also model systems for genomic and ecological analysis. Here, we present the complete genome assemblies of Saccharomyces jurei, a newly discovered Saccharomyces sensu stricto species from high altitude oaks. Phylogenetic and phenotypic analysis revealed that S. jurei is more closely related to S. mikatae, than S. cerevisiae, and S. paradoxus . The karyotype of S. jurei presents two reciprocal chromosomal translocations between chromosome VI/VII and I/XIII when compared to the S. cerevisiae genome. Interestingly, while the rearrangement I/XIII is unique to S. jurei, the other is in common with S. mikatae strain IFO1815, suggesting shared evolutionary history of this species after the split between S. cerevisiae and S. mikatae . The number of Ty elements differed in the new species, with a higher number of Ty elements present in S. jurei than in S. cerevisiae . Phenotypically, the S. jurei strain NCYC 3962 has relatively higher fitness than the other strain NCYC 3947 T under most of the environmental stress conditions tested and showed remarkably increased fitness in higher concentration of acetic acid compared to the other sensu stricto species. Both strains were found to be better adapted to lower temperatures compared to S. cerevisiae .